2021
DOI: 10.1002/cnr2.1471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the therapeutic effect of lenvatinib against advanced hepatocellular carcinoma by measuring blood flow changes using contrast‐enhanced ultrasound

Abstract: Background: The antitumor effect of a drug is considered to be associated with a decrease in tumor blood flow.Aims: We investigated whether the efficacy of lenvatinib (LEN) could be accurately assessed by measuring blood flow in hepatocellular carcinoma (HCC) during early treatment stages.Methods and results: Blood flow changes and treatment results of 19 patients who underwent contrast-enhanced ultrasound (CEUS), before and after LEN administration, in Kurume University Hospital from July 2018 to June 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…CEUS is a simple tool that can predict the therapeutic response of chemotherapy for diverse malignancies such as HCC, renal cell carcinoma, gastric carcinoma, and gastrointestinal stromal tumor [25][26][27]. CEUS can evaluate tumor necrosis and decreased blood flow inside the tumor more accurately than CT and MRI, and it is useful as an early therapeutic response evaluation tool in u-HCC cases treated with SOR and LEN [16,17,[28][29][30]. In par- ticular, SOR and LEN are considered to be suitable drugs for early evaluation by CEUS, because anti-tumor effects due to antiangiogenic effects appear early after the start of administration.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS is a simple tool that can predict the therapeutic response of chemotherapy for diverse malignancies such as HCC, renal cell carcinoma, gastric carcinoma, and gastrointestinal stromal tumor [25][26][27]. CEUS can evaluate tumor necrosis and decreased blood flow inside the tumor more accurately than CT and MRI, and it is useful as an early therapeutic response evaluation tool in u-HCC cases treated with SOR and LEN [16,17,[28][29][30]. In par- ticular, SOR and LEN are considered to be suitable drugs for early evaluation by CEUS, because anti-tumor effects due to antiangiogenic effects appear early after the start of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Funaoka et al [ 87 ] reported that Sonazoid CEUS was helpful for evaluating HCC after radiation treatment. After treating HCC with systemic agents such as sorafenib, Sonazoid CEUS was helpful in predicting treatment response by examining perfusion parameters or evaluating enhancement architecture [ 88 89 90 91 ]. However, most studies considered fewer than 50 patients and had preliminary study designs in which evaluation parameters were not established.…”
Section: Questions and Recommendationsmentioning
confidence: 99%
“…51 As lenvatinib strongly decreases the blood perfusion early after administration, several studies have used the contrastenhanced ultrasound with high temporal resolution to assess the tumor hemodynamics and early response to treatment. [52][53][54] Dynamic contrast-enhanced MRI under free-breathing using a stack-of-stars technique was developed as a method to evaluate the blood perfusion over time, and may be applied in the future to evaluate the early therapeutic effect of HCC after lenvatinib administration. 55,56 Evaluation of Treatment Response after ICI (Fig.…”
Section: Y Tsujita Et Almentioning
confidence: 99%